Mesenteric panniculitis associated with non-alcoholic fatty liver disease: a case series - Mehreen Siyal; Zaigham Abbas; Alina Saeed; Muhammad Ali Qadeer (Journal of the Pakistan Medical Association)
Mesenteric panniculitis (MP) is a benign inflammatory condition of the abdominal mesentery which presents with a wide variety of symptoms. It is diagnosed non-invasively through computed tomography (CT) scan, whereas biopsy is still considered the gold standard. Steroids are the first line of treatment. Here, we report four cases who presented with abdominal pain. These patients were overweight and the CT scan findings were suggestive of mesenteric panniculitis. Three cases had concomitant non-alcoholic steatohepatitis with elevated alanine transaminase levels, dyslipidaemia, and insulin resistance. FibroScan showed moderate to severe steatosis. PNPLA3 rs738409 genotype was homozygous positive (GG) in one patient, whereas two patients were heterozygous positive (CG). This association has not been well-described so far and warrants further investigation. There may be some common predisposing factors.